Impact of gut microbiota and immune contexture on effectiveness of neo-adjuvant chemo-radiotherapy in locally advanced rectal cancer (LARC). (1st June 2022) - Roesel, R; Basso, C; Epistolio, S; Djordjevic, J; Sorrenti, E; Terzaghi, L; Galafassi, J; Spina, P; Popeskou, S G; Mongelli, F; Frattini, M; Iezzi, G; et al.
Abstract: Objective: Among patients affected by Locally Advanced Rectal Cancer (LARC), 15–20% ultimately reveal a complete pathological response to the neo-adjuvant chemo-radiotherapy nCRT), which might render the surgical resection no longer necessary. However, the possibility to adopt alternative management options, such as a "wait and see" strategy, is hampered by the lack of reliable indicators of complete responsiveness to nCRT. Our hypothesis is that the composition of LARC-associated microbiome and immune contexture may predict the responsiveness to nCRT. We therefore proceed to a quantitative and qualitative evaluation of gut microbiome composition and immune contexture in LARC bioptic tissues and we then comparatively evaluated those markers in complete responders (Tumor regression grade, TRG, 1) versus others (TRG2-3-4). Methods: FFPE (Formalin Fixed Paraffin Embedded) LARC tissues from diagnostic biopsies and corresponding resections from patients treated at our hospital from 2012 to December 2019 were collected. Following sample deparaffinization, n. 71 genomic DNA (gDNA) and total cellular RNA were extracted. DNA used for microbiome analysis, upon amplification and sequencing of the hypervariable V3-V4 region of 16S gene. Expression of immune cell genes was evaluated by the Nanostring PanCancer Immune profiling panel on extracted RNA. Results: Regarding the Microbiome profile we found no difference in terms of biodiversity between complete responders and others. However, we found some species significantly disregulated, in particular an over-expression of Alloprevotella Rava and down-expression of Porphyromonas Asaccharolytica, Turicibacter Sanguinis, Leptotrichia Trevisanii, Fusobacterium Nucleatum. The immune contexture analysis revealead a significant disregulation of 41 genes. Conclusion: FFPE tissues from diagnostic biopsies proved suitable for the analysis of LARC-associated microbiome and immune contexture. A specific microbiome signature appears to be associated with responsiveness to neo-adjuvant chemoradiotherapy. Defined immune related genes, in particular those associated with IFN-gamma response, are up-regulated in tumors exhibiting complete response. A possible associations between the bacterial species significantly disregulated and this favorable immune contexture is currently under investigation.